Spodnjetriasni fosili med Sveto Barbaro in Osolnikom - Križnar, Matija (Loški razgledi, 2013)
The ridge between Sveta Barbara and Osolnik has been known as a site for fossils for a number of years. All fossils, mainly the remains of cephalopods, were found in Lower Triassic layers. Although geological research was carried out more than a hundred years ago, no fossil finds from this area were reported. Our fieldwork focused on fossil bearing Lower Triassic layers, which have been uncovered by many cart tracks, occasional steeps or streams. We found many fossil remains of cephalopods, bivalves, gastropods, crinoids, teeth of vertebrates and trace fossil.
Keywords: paleontologija; paleontology; geologija; geology; fosili; fossils; spodnji trias; trias; Škofja Loka; Slovenia; Slovenija